Quick understanding of clay-sand stabilization in strength performance assessment on CBR and UCT tests - Muhammad, Toyeb; Andriani, Andriani; Muhammad Shubhi, Nurul Hadie; Muhammad, Alfin; Rizki Ramadhan, Husaini; Muhammad, Lutfi; Alsidqi, Hasan (EDP Sciences, 2025)
The clay contain is fine-grain fractions with low bearing capacity. The clay can be improved by adding sand as coarse-grains. Incorporate the sand in clay mixture does not always exhibit the same trend of increasing in strength from different mechanical tests. This study aims to quickly understand the effective sand content in clay soil by UCT and CBR tests. Clay mixed with two sand contents of 10% and 20%. The samples are cured for four days before testing. According to the USCS method, the clay has a high plasticity index (CH). Meanwhile, sand is classified in the sand group with a small number of fine-grains. Clay-sand stabilized obtained an increase in strength with a positive trend using the CBR test but has a negative trend when using UCT. The unconfined compressive strength decreases at an additional 20% sand content. Presence the coarse fraction and decrease in cohesiveness of clay, as well as unconfined samples condition lead a decrease in compressive strength. Therefore, it can be emphasized that UCT is only suitable for clay or cohesive soils with effective sand content of 15% maximum.